Evidence for Polarized Solar Flare Emission From Simultaneous Radio Observations in Australia and Vietnam - Thao, Nguyen Thi; Phuong, Nguyen Thi; Darriulat, Pierre; Diep, Pham Ngoc; Hoai, Do Thi; Nhung, Pham Tuyet; Anh, Pham Tuan (Communications in Physics, 2015)
A sample of 34 solar flares recorded in Ha Noi using the VATLY radio telescope between April 2012 and January 2014 at frequencies of 1415 and 1417.6 MHz is compared with the corresponding observations made at 1415 MHz by the solar observatory of Learmonth (Australia). While good overall agreement is obtained, a few differences are noted and studied in some detail. In particular, the use of different feeds in Ha Noi and Learmonth reveals a case of very large polarization of the flare emission.